Experiences of physical activity: A phenomenological study of individuals with cystic fibrosis. (February 2016) - Street, Rachael; Mercer, Jenny; Mills-Bennett, Rebekah; O'Leary, Catherine; Thirlaway, Kathryn
Although extensive research has investigated the benefits of physical activity in cystic fibrosis, minimal exploration of the experiences for individuals from a qualitative, phenomenological perspective has been carried out. The aim of this study was to explore the subjective experiences of physical activity for individuals with cystic fibrosis. The health-care team, at an Adult Cystic Fibrosis Unit in the United Kingdom, recruited 12 participants to take part. Interview data were analysed using interpretative phenomenological analysis. A central theme of 'self-monitoring' emerged from the accounts and was embedded in the three super-ordinate themes.